NEO-COLONIAL DISCOURSE AND THE EUROPEANISATION PARADOX: THE OHR’S BONN POWERS AND DEMOCRATIC REGRESSION IN BOSNIA AND HERZEGOVINA - Sajić, Nina; Vranješ, Aleksandar (Politeia, 2026)
Bosnia and Herzegovina presents a central paradox of Europeanisation: while the country has formally advanced on the EU path, it remains subject to an external executive authority whose powers are difficult to reconcile with democratic accountability and the rule of law. Bosnia and Herzegovina was granted EU candidate status in December 2022, and in March 2024 the European Council decided to open accession negotiations, while inviting the Commission to prepare the negotiating framework. Yet the OHR continues to impose legislation, amend constitutional arrangements, and dismiss elected officials without democratic mandate, practices the European Commission itself condemned in 2019 as “in principle incompatible with the sovereignty of Bosnia and Herzegovina and therefore with EU membership.” This article argues that the Office of the High Representative (OHR) in Bosnia and Herzegovina functions as a neo-colonial institution whose exercise of executive authority through the extra-legal “Bonn Powers” systematically undermines the conditions for meaningful EU integration. Drawing on neo-colonial theory, the article examines the legal basis of the Bonn Powers, their use by successive High Representatives, and the EU’s response to their continued application under Christian Schmidt. It shows that the EU is pursuing Bosnia and Herzegovina’s accession while tolerating a form of external governance that contradicts the democratic and rule-of-law standards of that process. This structural double standard has produced what the article terms a Potemkin democracy: a system in which the formal institutions of democratic governance operate as a façade while actual authority remains vested in an externally appointed and unaccountable official.